Thank you, Mr. Falker - Polacco, Patricia (New York : Philomel Books, 1998)
At first, Trisha loves school, but her difficulty learning to read makes her feel dumb, until, in the fifth grade, a new teacher helps her understand and overcome her problem.
Wilson's Children, October 2010.
Elem. School Library Collection, June 2000.
School Library Journal, June 1998.
Book Links (A.L.A.), February 2003.
Publisher's Weekly, April 1998.
Booklist, May 1998.
Keywords: Reading -- Fiction; Teachers -- Fiction; Learning disabilities -- Fiction; Reading disability -- Fiction; Reading -- Fiction; Teachers -- Fiction; Learning disabilities -- Fiction; Reading disability -- Fiction; Reading -- Fiction; Teachers -- Fiction